2014
DOI: 10.1177/0956797614544307
|View full text |Cite
|
Sign up to set email alerts
|

Gaze Following Is Accelerated in Healthy Preterm Infants

Abstract: Gaze following is an essential human communication cue that orients the attention of two interacting people to the same external object. This capability is robustly observed after 7 months of age in full-term infants. Do healthy preterm infants benefit from their early exposure to face-to-face interactions with other humans to acquire this capacity sooner than full-term infants of the same chronological age, despite their immature brains? In two different experiments, we demonstrated that 7-month-old preterm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 38 publications
4
26
3
1
Order By: Relevance
“…Therefore, the discrepancy between our results and Peña et al. () in gaze following of preterm infants might be explained by gestational age difference.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, the discrepancy between our results and Peña et al. () in gaze following of preterm infants might be explained by gestational age difference.…”
Section: Discussioncontrasting
confidence: 99%
“…In a series of experiments, Peñ a and colleagues showed that the loss of sensitivity to suprasegmental and segmental features of a foreign language that normally occurs during the first year of life was not dependent on the duration of exposure to broadcast speech (Peñ a et al, 2010(Peñ a et al, , 2012. In contrast, sensitivity to the phonotactic rules of the native language varies with the duration of postnatal experience (Gonzalez-Gomez and Nazzi, 2012), as do a number of visual functions including binocular perception (Jandó et al, 2012) and gaze following (Peñ a et al, 2014). These variations should not be viewed as inconsistent but as pertinent dissociations shedding light on how these computations are realized in vivo.…”
Section: Exploring the Possible Role Of Maturational Tempomentioning
confidence: 99%
“…On notera aussi que l'acquisition du langage dépend également du traitement d'autres modalités perceptives, notamment de certains aspects du traitement visuel, comme la capacité à fixer les lèvres ou les yeux de la personne qui parle, et l'attention jointe (entre un enfant, l'adulte qui lui parle et l'objet qui est par exemple désigné par l'adulte). Ainsi, les similitudes et les différences observées dans le dévelop-pement du traitement visuel entre enfants nés à terme et enfants prématurés [39,40] devraient aussi contribuer à moduler les trajectoires d'acquisition langagière dans ces deux populations.…”
Section: Assembler Les Pièces Du Puzzleunclassified